Analysis of Alginate Implants Degradation Rate in Rat Myocardium - Shkand, Tatyana V.; Tatarets, Anatoliy L. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):173.